2018
DOI: 10.1590/0037-8682-0352-2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five methods of extraction of Staphylococcus aureus DNA for molecular detection by PCR

Abstract: Although one protocol seemed more efficient than the others, PCR was sensitive enough to allow for detection of S. aureus with all the protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The higher male incidence is poorly understood and requires further research to identify correlated hazard agents. The result obtained from the extraction of DNA remained in accordance with the study done by Lara et al [21]. Jaffe et al [22] found that the median concentration of isolated DNA of S. aureus was 78.5 ng/µl, the difference between the results of this study and the results obtained from the current study may be explained by the use of larger quantities of bacteria in higher concentrations of DNA and kits used in DNA extraction.…”
Section: Discussionsupporting
confidence: 91%
“…The higher male incidence is poorly understood and requires further research to identify correlated hazard agents. The result obtained from the extraction of DNA remained in accordance with the study done by Lara et al [21]. Jaffe et al [22] found that the median concentration of isolated DNA of S. aureus was 78.5 ng/µl, the difference between the results of this study and the results obtained from the current study may be explained by the use of larger quantities of bacteria in higher concentrations of DNA and kits used in DNA extraction.…”
Section: Discussionsupporting
confidence: 91%
“…A molecular analysis of phenotypically identified S. aureus isolates was performed by amplification of the Staphylococci 16s rRNA gene, the species-specific nuc gene and the mecA -resistant gene. The genomic DNA was extracted using the DNA extraction method CTAB (Cetyltrimethylammonium bromide) ( Maristela Oliveira Lara et al, 2018 ). Before molecular analysis, the extracted DNA was analyzed using gel electrophoresis (1%).…”
Section: Methodsmentioning
confidence: 99%
“…The PCR cycling conditions (Thermal profile) were in the order: Initial denaturation at 94˚C lasted 10 minutes; 35 cycles of amplification at 94˚C lasted for 30 seconds; annealing at 53˚C lasted for 30 seconds; extension at 72˚C lasted for a minute and finally, extension at 72˚C lasted for 5 minutes. Amplification products were analyzed on a 2.0% agarose gel electrophoresis prepared by 2 g of gel to 100 mls of TAE buffer for efficient separation [27].…”
Section: Sample Collection and Processingmentioning
confidence: 99%